The interneuron energy hypothesis: Implications for brain disease - Kann, Oliver (Neurobiology of disease, 2016)
Fast-spiking, inhibitory interneurons - prototype is the parvalbumin-positive (PV+) basket cell - generate action potentials at high frequency and synchronize the activity of numerous excitatory principal neurons, such as pyramidal cells, during fast network oscillations by rhythmic inhibition. For this purpose, fast-spiking, PV+ interneurons have unique electrophysiological characteristics regarding action potential kinetics and ion conductances, which are associated with high energy expenditure. This is reflected in the neural ultrastructure by enrichment with mitochondria and cytochrome c oxidase, indicating the dependence on oxidative phosphorylation for adenosine-5′-triphosphate (ATP) generation. The high energy expenditure is most likely required for membrane ion transport in dendrites and the extensive axon arbor as well as for presynaptic release of neurotransmitter, gamma-aminobutyric acid (GABA). Fast-spiking, PV+ interneurons are central for the emergence of gamma oscillations (30-100Hz) that provide a fundamental mechanism of complex information processing during sensory perception, motor behavior and memory formation in networks of the hippocampus and the neocortex. Conversely, shortage in glucose and oxygen supply (metabolic stress) and/or excessive formation of reactive oxygen and nitrogen species (oxidative stress) may render these interneurons to be a vulnerable target. Dysfunction in fast-spiking, PV+ interneurons might set a low threshold for impairment of fast network oscillations and thus higher brain functions. This pathophysiological mechanism might be highly relevant for cerebral aging as well as various acute and chronic brain diseases, such as stroke, vascular cognitive impairment, epilepsy, Alzheimer's disease and schizophrenia.
Available online 16 August 2015
Gesehen am 07.05.2020